2019
DOI: 10.33403/rigeo.573470
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Opinions of 7th Grade Students on Intangible Cultural Heritage

Abstract: The purpose of this study is to identify the opinions of 7 th grade students at middle schools on the elements of intangible cultural heritage (ICH) and to reveal their levels of awareness on such elements. The study based on qualitative research method was carried out through qualitative research design. The study group consists of 13 students studying at a school at the city center of Bartın. Data of the study were obtained from focus group interviews held with students. The data were analyzed through conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Regarding content, 9 studies were identified that focus on intangible heritage and show the didactic applications of teachers through oral presentations of legends, stories, and rituals that are part of the cultural identity of students. Teachers use resources such as documentary reviews through written texts, websites, and Android-based applications [45,46]. Regarding teacher behavior, an active, guiding, and innovative role is highlighted [47,48], coinciding with 18 studies, with the constructivist approach being the most used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding content, 9 studies were identified that focus on intangible heritage and show the didactic applications of teachers through oral presentations of legends, stories, and rituals that are part of the cultural identity of students. Teachers use resources such as documentary reviews through written texts, websites, and Android-based applications [45,46]. Regarding teacher behavior, an active, guiding, and innovative role is highlighted [47,48], coinciding with 18 studies, with the constructivist approach being the most used.…”
Section: Resultsmentioning
confidence: 99%
“…However, the levels of heritage development that should be instilled in the students are not achieved [48,56,57]. In addition, the studies analyzed focus on formative activities within the classroom, unlike other authors who argue that outdoor learning and museum visits promote greater learning by adopting a holistic vision that encompasses history, nature, tradition, and culture, facilitating proximity to the student's environmental and sociocultural reality [5,30,46,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] state the pressing need to train teachers in such a way that they have the necessary knowledge related with the teaching of heritage. Faced with such problems, it is easy to accept that the decisive idea lies in active learning, based on a participatory methodology in which the reasoning and considerations of students are given priority [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been predominantly carried out with students, teachers, and teacher candidates. It can be seen that the students' knowledge, viewpoint, perception, attitude, and awareness of the areas relevant to cultural heritage were assessed in the studies of the first group (Akkaya, 2017;Arıkan and Doğan, 2013;Aslan ve Çulha, 2008;Dönmez and Yeşilbursa, 2014;Gürdoğan-Bayır and Çengelci-Köse, 2019;Gürel and Çetin, 2019;Ismaeel and Al-Abdullatif, 2016;Karakuş, Çepni and Kılcan, 2011;Levy, 2016;Sağ and Ünal, 2019;Tuncel and Altuntaş, 2020;Uztemur, Dinc and Acun, 2019). In second group studies have focused on the insights of teachers in different branches on cultural heritage issues and its teaching (Adukaite, van Zyl, Er and Cantoni, 2017;Avcı and Memişoğlu, 2016;Giménez, Ruiz and Listán, 2008;Kafol, Dena and Znidarsic, 2015;Lee and Bang, 2011;Levy, 2016;Özlek, 2019;Pérez, López and Listán, 2010).…”
Section: Introductionmentioning
confidence: 99%